Microcosm of interlinking between agriculture, climate change, policies and regulations: a case study of Bundelkhand region - Singh, Indra Kumar (The journal of contemporary issues in business and government, 2021)
As per report of an International Energy Agency ,India emitted CO2 to the tune of 2,299 million in 2018.Of the gross national emission 18% is contributed by Agriculture and livestock. Although the agricultural sector is liable for GHG emission led climatic change but it bears the brunt of the change to a far greater extent than other major contributors. India is a member of Food and Agriculture Organisation of the United Nations, International Plant Protection Convention was signed in 1952 by India and ratified on 9 June, 1952 so the intention is apparent to not fall behind in international regime of regulations and conventions. However the particular hardships faced in our country are peculiar and political will and the policies to surpass the same is paramount to overcome them.